Energy harvesting using flexible piezoelectric materials from human walking motion: Theoretical analysis - Cha, Youngsu (SAGE PUBLICATIONS LTD, 2017)
Human walking is a good energy source that can be harvested to support wearable devices. For one walking cycle, the muscles at each joint of human lower body consume tens of watts. The considerable amount of kinetic energy generated while walking can be turned to useful electric energy through energy transducers. In this article, we theoretically investigate energy harvesting from flexible piezoelectric materials attached to humans while walking. We focus on the hip, knee, and ankle motions of walking humans and analyze the frequency characteristic of the motions using Fourier series fitting. A model is utilized to predict the electrical responses from piezoelectric materials and the power harvested through load resistances. In particular, we estimate the harvested power from polyvinylidene fluoride and derive the contour maps with respect to the harvested power as a function of the load resistance and walking frequency. Moreover, we discuss the necessary mechanical power input required to deflect the energy harvester and the effects of the varied parameters.
Keywords: GENERATING ELECTRICITY; COMPOSITES